APLIKASI PEMESANAN MENU PADA KAFE KOPIGALAU BERBASIS ANDROID - Rizqi Aziizi Ros Atmaja (2020)
Current technological developments are very helpful for users in carrying out activities, not least for the activities of cafe businesses. The large number of cafes that exist today makes the cafe owner must find ideas and implement the right strategy in getting the attention of consumers. At this Kopi Galau cafe is a cafe that sells a variety of drinks and snacks. Kopi Galau cafe has the main target of young people, therefore the cafe wants to always bring something creative and unique to attract young people. However, the ordering process is still done face-to-face and conventional, sometimes making orders that are not right, not fast enough, miscalculated and there are ordering errors. So that the current system is less effective and efficient. Therefore, to prevent these problems, the authors make a Menu Ordering Application at Kopi Galau Cafe which is expected to help the cafe in carrying out the menu ordering process. By using an android-based application on the client side and integrated with the android-based application on the server side at the cafe to manage orders.